Molecular MRI with hyperpolarized xenon and smart sensors - Hegarty, Ryan Patrick (2018)
The main aim of this project was to develop an understanding of both the theoretical and experimental aspects of MRI and NMR spectroscopy, while also gaining expertise in hyperpolarized xenon MRI methods.